Prevalence of Co-Infections and Pathogens in Hospitalized Children with Acute Respiratory Infections: A Comparative Analysis Between SARS-CoV-2 and Non-SARS-CoV-2 Cases - Visal Moolasart MD; Ravee Nitiyanontakij MSc; Srisuda Samadchai MNS; Somkid Srisopha MSc; Priyanut Atiburanakul MD; Suthat Chottanapund MD; Sumonmal Uttayamakul PhD (SAGE Publishing, 2024)
Objectives. We aimed to compare the prevalence of co-infections, pathogens, and factors associated with SARS-CoV-2 acute respiratory infection (ARI) and non-SARS-CoV-2 ARI, among hospitalized children. Methods. We conducted an observational cross-sectional study of hospitalized children <15 years with ARI, and lasting respiratory symptoms <14 days, using polymerase chain reaction on nasopharyngeal specimens. Results. Of the 184 children with ARI analyzed, 122 were infected with SARS-CoV-2 and 62 were not. SARS-CoV-2 ARI had a significantly lower rate of co-infection than non-SARS-CoV-2 ARI (2.5% vs14.5%, P  = .003). SARS-CoV-2 ARI children were significantly associated with a less empirical antibiotics (aOR = 0.09, CI = 0.03-0.21; P  = .000), more pneumonia (aOR = 5.15, CI = 1.77-14.95; P  = .003), and more abnormal chest X-ray (aOR = 2.81, CI = 1.38-5.71; P  = .004). Conclusions. Although SARS-CoV-2 ARI in hospitalized children was associated with pneumonia and abnormal chest x-rays, empirical antibiotics may not be necessary for treating mild to moderate cases.